Frequency analysis of annual one day to five consecutive days maximum rainfall for Gandak river basin - Singla, Shivika; Halder, Raktim; Khosa, Rakesh; Singla, Rumani; Rajeev, Rudraksh (International Journal of Engineering and Technology, 2014)
The present study has been conducted for rainfall intensity and frequency estimation for the Gandak basin, a region prone to high floods with an unrealized and unexplored hydro-potential. The two popular gridded precipitation datasets i.e.: (1) APHRODITE, and (2) IMD, for the years 1969-2005, has been used to calculate the mean basin precipitation through the Thiessen polygon method on the ARC-GIS interface. This computed data was used to find out the 1-day, 2-day to 5-day consecutive maximum precipitation series and hence fitted into various well-known probability distribution functions viz., Normal, Gamma, Exponential, etc. According to the best fit data in these functions, the quantiles were determined corresponding to a return period of 2, 10, 20, 25, 50 and 100 years. The two widely used tests: Chi-square Test and Kolmogorov-Smirnov Test were employed to further check the goodness of fit of the series in the distributions. The results reveal that the best fit for 1-day was achieved with the normal distribution, for 2-day with GEV and with GPAR for the remaining maximum consecutive days rainfall. Such studies have thus proven to be substantially facilitative in planning for the safe and economic design of various engineered structures such as bridges, culverts, levees, canals, irrigation and drainage works and effective reservoir management.